Modeling Passengers’ Boarding Behavior at the Platform of High Speed Railway Station - Tie-Qiao Tang; Yi-Xiao Shao; Liang Chen; Hua-Yan Shang (Journal of Advanced Transportation)
Modeling passengers’ motion at high speed railway (HSR) station has been a hot topic in the field of pedestrian flow theory. However, little effort has been made to explore the passengers’ boarding behaviors at the platform of HSR station. This study proposes a cellular automaton (CA) model to study the passengers’ boarding behavior at the platform of HSR station. Some numerical tests are conducted to explore the passengers’ movements and the complex traffic phenomena (e.g., each passenger’s trajectory, congestion, and travel time) which occur during the boarding process. The numerical results illustrate that the passengers’ inflow rate and entrance choice behavior have significant impacts on the boarding efficiency. These results can help managers to understand the passengers’ boarding behavior and to improve the boarding efficiency.